TEKNOLOGI INFORMASI PEMBENTUK MULTIPLIER EFFECT DALAM BISNIS CORPORASI - Marius Robert Seran; David Kaluge (Journal of Management Small and Medium Enterprises (SMEs), 2016)
Business corporation must use all of its own resources to face the competitive rivalry in globalizedworld. Information is one of the fundamental thing in business. The application of technology inmanaging information is one of the fomula that can make multiplier effect in business activities.Intervention of information technology through four functions of management, Planing,Organizing, Actuating and Controlling, will influence the operational activities of corporation to beefficient and effective, and create the competitive advantage of the corporation. The multiplier effectcreated by intervene of information technology in business corporation consists of 1. Differentiation;2. Easy of Marketing; 3. Increasing of Productivity; 4. Efficiencies of Cost and Time; 5. Consistencyand Quality Assurance.Keywords : Information Technology, Multiplier Effect